AUTOMATIC TRASH BOX MENGGUNAKAN SENSOR ULTRASONIK BERBASIS ARDUINO UNO - Putri, Amanda Tsabita; Ramadhan, Noer; Sulistia; Anugraha, Nurhajar (Teknik Elektro Polsri, 2024)
The designed tool is capable of automatically opening the cover of the garbage box when it detects the presence of the user around it. They also performed tools testing and cost analysis for this research. The results show that this tool can work well and can help in waste management. Nevertheless, further testing of ultrasonic sensors and ports is needed to identify and correct any problems that may arise. Further development of program codes is also needed to improve the accuracy and reliability of the system in responding to proximity objects. Lastly, security and reliable aspects of systems in everyday use need to be taken into account, as well as environmental factors that may affect system performance. Thus, this automatic trash tool is expected to help manage garbage more effectively and efficiently.